Olive Cultivation - Yonar, Taner (IntechOpen, 2022)
The olive plant has served as a source of food and even healing for thousands of years, especially in the Mediterranean Basin. It is also the source of livelihood for many people in the countries surrounding the Mediterranean Sea. This book highlights the importance of olives with chapters addressing olive fertilization, production, management, harvesting, and enrichment.